Planned and unplanned pregnancies in breast cancer survivors. (August 2019) - Kopeika, Julia; Bhaduri, Mahua; Kugadas, Anija; Reddy, Nivedita; Shewbridge, Amanda; Mukherji, Deborah; Sandri, Ines; Mansi, Janine
Abstract: Background: Nearly 20% of women presenting with breast cancer in the UK are of reproductive age. The aim of our study was to assess fertility outcome in relation to intent to conceive in patients who had completed breast cancer treatment. Methods: Between July 2011 and December 2013, women, aged less than 43 years at the time of diagnosis, were asked during their follow-up in breast cancer clinic, to complete a questionnaire on intentions to conceive and pregnancy outcome. Results: A total of 175 women completed the questionnaire at a median time of 6 years from time of diagnosis. Their median age at the time of diagnosis was 37 years and at the time of the survey was 43 years. At the time of the survey, 42% (72/175) had completed their family, 41% (72/175) reported that they would like to have children and 4% (7/175) did not wish to have children. Twenty-seven respondents had actively tried to conceive, and of those 13 (48%) had a live birth. There were 12 unintended pregnancies; the majority of which were terminated (58% (7/12)) with only 3 live births. Among those who did not wish to conceive, only 32% (36/111) reported using contraception. Conclusion: This is a retrospective study investigating menstrual function, contraceptive methods and fertility outcomes of young breast cancer survivors. This study highlights the need for healthcare professionals to provide long-term contraceptive advice to women who do not wish to conceive. Highlights: At least 40% of women diagnosed wit breast cancer under the age of 43 still desire to conceive after completing cancer treatment. Large proportion of women who did not use contraception in spite of having regular periods and reporting no intention to conceive. This study established an unexpected high proportion of unintended pregnancies, 58% of which required terminated. Its imperative for healthcare professionals to provide patients with advice not only on fertility but also contraception during and after chemotherapy.